Efektivitas Kebijakan Peraturan Walikota Kupang Nomor 33 Tahun 2019 Tentang Pengurangan Penggunaan Kantong Plastik (Studi Kasus: Kota Kupang) - Ni Putu Eka Ananda; William Djani; Made N. D. Andayana; Ernestus Holivil (Multidisciplinary Journal of Religion and Social Sciences, 2026)
This study aims to analyze the effectiveness of the implementation of Kupang Mayor Regulation Number 33 of 2019 concerning the Reduction of Plastic Bag Usage and to identify the obstacles encountered in its implementation in Kupang City. This research employs a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation in traditional markets, shopping centers, and among micro, small, and medium enterprises (MSMEs) in Kupang City. Data analysis was conducted qualitatively using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. Data validity was tested through triangulation techniques. The results indicate that the implementation of Kupang Mayor Regulation Number 33 of 2019 has not been effective. Low levels of understanding among the public and business actors regarding the policy, limited socialization, weak supervision, and the lack of affordable environmentally friendly bag alternatives are the main factors hindering the success of the policy. The use of single-use plastic bags is still widely found, particularly in traditional markets and the MSME sector, indicating that the objective of reducing plastic waste generation has not yet been optimally achieved.